Diseño de plan estratégico para la formalización de la comunicación interna en Adiela de Lombana S.A (2018)
Adiela de Lombana is a Valle del Cauca organization founded in 1986 dedicated to the commercialization and installation of products for light construction. Its main headquarters are located in the city of Cali. In addition, it has presence in different cities of Colombia. Adiela de Lombana S.A. through the design of a Strategic Internal Communication Plan. For execution, four main variables were taken into account, which were: identifying information flows, channels and means of communication; establish the characteristics of the media communication of the organization and characterize the organizational culture. During the approaches that were taken with the company it was identified that the difficulty was the lack of communication management within the organization. As a consequence of the above, the channels are not being executed in an effective way. In order to comply with the objective of the response and the problem, at the first moment, the pertinent information about ADL SA is collected through a survey, structured by the following: organizational culture and addressing, group communication, interpersonal communication, communication with leaders and communication channels. Once the survey was applied, the analysis of the results of the work direction towards the fulfillment of each one of the proposed objectives was initiated. The management of the communication in the organization, the little information of the strategic direction, the outdated channels. Communication and lack of protocols in communication processes. As a final step, recommendations were given in the field of communication such as strengthening internal spaces and channels through the activation and updating of content that improves the flow of information. As well as, the realization of different activities that strengthens the interpersonal relationships between collaborators and leaders